Vai trò của giá trị cá nhân về sự hòa hợp trong việc giảm thiểu mức độ tác động tiêu cực của căng thẳng lên công việc và cuộc sống của nhân viên y tế - Mai Thị Mỹ, Quyên; Phạm Ngọc Trâm, Anh (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
Healthcare professionals, especially physicians, typically experience high levels of job stress which not only undermines their job engagement but also negatively affects their personal lives. Acknowledging the inherent job stress faced by physicians, this research investigates the roles of value to social integration in enhancing their job engagement and quality of life. Based on survey data from 352 physicians, the results of structural equation modeling show that while job stress hinders both job engagement and quality of life, value to social integration helps to foster these two aspects. Furthermore, value to social integration moderates the negative impact of job stress on job engagement, as well as the impact of job engagement on quality of life. The theoretical and practical implications of the study are then discussed accordingly.
Keywords: Personal value; Value to social integration; Job stress; Job engagement; Quality of life; Physician